ANALISIS PERAN ORANGTUA PENAMBANG EMAS TERHADAP PENDIDIKAN ANAK DI PERGURUAN TINGGI DESA NANGA SERIAN - Wahyuni, Sri; Imran, Imran; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out about, "the role of parents of gold miners in the education of children in tertiary institutions of Nanga Serian Village, Kapuas Hulu Regency". The research method used is descriptive form of qualitative research. Data source of research of parents who have children in college. Data collection techniques used observation, interview and documentation techniques, while the data collection tools used observation and interview guides. The analysis in this research was presented in a descriptive qualitative manner using 4 informants. 1. What is the role of the parent of a gold miner as an educator in the education of children in higher education. 2. How is the role of gold miners 'parents as facilitators of children's education in tertiary institutions; 3. What is the role of gold miners' parents as motivators of children's education in tertiary institutions. The results of the study 1. The role of parents of gold miners as educators of children's education in higher education in the form of parents who remind children to always learn. 2. The role of parents of gold miners as facilitators of children's education in higher education in the form of parents providing shelter, mobile phones, notebooks, motorcycles. 3. The role of parents as a motivator for children's education in higher education in the form of full support from parents to their childrenÂ Keywords: Role Parents, Children Education, College